Never ready: Addictions counselors dealing with client death. (30th May 2022) - Sperandio, Katharine R.; Goshorn, Jeremy R.; Moh, Yoon Suh; Gonzalez, Edith; Johnson, Nicole G.
Abstract: This study explored the experiences of addictions counselors who have undergone client death and the immediate and long‐lasting impacts of client death on addictions counselors through the consensual qualitative research (CQR) method. We conducted semistructured interviews with 10 participants exploring their lived, in‐depth, experiences in working with clients with addictive disorders with focus given to the death of clients and how they responded to the experience. Results from a data analysis process using the CQR method indicate eight domains: (a) professional ethics, (b) coping skills, (c) client care, (d) preparation for profession, (e) experience of addiction, (f) agency impact, (g) exploring the death experience, (h) recommendations, and 28 categories embedded in each of these domains. Implications for counselor education, training, and practice are discussed.